Forebrain-specific trkB-receptor knockout mice: behaviorally more hyperactive than “depressive” - Zörner, Björn; Wolfer, David Paul; Brandis, Dorothee; Kretz, Oliver; Zacher, Christiane; Madani, Rime; Grunwald, Ilona; Lipp, Hans-Peter; Klein, Rüdiger; Henn, Fritz A.; Gass, Peter (Biological psychiatry, 2003)
Background - According to the neurotrophin hypothesis of depression, decreased activity of brain-derived neurotrophic factor (BDNF) contributes to behavioral and plasticity-related alterations in depressed patients. We investigated the hypothesis that mice with a forebrain-specific knockout of the trkB receptor, the main mediator of BDNF signaling, represent a genetic animal model for depression. - Methods - Using the CRE-loxP system, we bred trkBCaMKII-CRE mice with a trkB-receptor disruption in the forebrain. We subjected trkB-mutant mice to a battery of behavioral tests, comprising open field, elevated zero maze, emergence test, novel object test, and forced swim. Additionally, we investigated the hypothalamic-pituitary-adrenal (HPA) axis immunohistochemically and by plasma analyses. - Results - trkBCaMKII-CRE mice showed a stereotyped hyperlocomotion with reduced explorative activity, and impulsive reactions to novel stimuli. The trkB-mutant mice did not exhibit depressionlike behaviors such as increased “despair” in the forced swim test, increased anxiety in the elevated zero maze, or neophobia in the novel object test. Furthermore, no HPA dysregulation was observed under normal and stressful conditions. - Conclusions - trkBCaMKII-CRE mice cannot be regarded as a genetic mouse model of depression. Instead, the behavioral symptoms of trkBCaMKII-CRE mice, comprising hyperlocomotion, stereotyped behaviors, and cognitive impairments, are similar to those postulated for mouse models of attention-deficit disorder.